Compact printed monopole antenna for ultra‐wideband application with dual band‐notched characteristic. Issue 11 (26th August 2013) - Sarkar, Manas; Dwari, Santanu; Daniel, Anitha
ABSTRACT In this article, a compact ultrawideband (UWB) microstrip‐fed printed monopole antenna with dual band‐notched characteristics is proposed. The proposed design consists of a radiating patch with semielliptical shape and the modified ground plane with two bevels on the upper edge of the ground plane to cause the wideband from 3.1 to 10.6 GHz for UWB application. In addition, cutting two semicircular slots on the bottom edge of the ground plane, operating band is further extended above 10.6 GHz. The band notch at the two bands 3.4–3.6 GHz and 5.6–5.8 GHz is achieved using a pair of concentric annular slots with splits in them in opposite side. Fine tuning is possible with adjusting the length and radius of those slots. The antenna size is 24 × 34.6 mm and designed using FR4 substrate having εr = 4.4 and thickness of 0.8 mm. Design and optimizations have been carried out using HFSS v13.0 and there is good agreement with measured results. The proposed antenna exhibits a nearly omnidirectional radiation pattern in the H‐plane, and a dipole‐like radiation pattern in the E‐plane for the entire pass band. © 2013 Wiley Periodicals, Inc. Microwave Opt Technol Lett 55:2595–2600, 2013